"Aunt Grace can't have babies" - Cox, A. James (Journal of religion and health, 1986)
One of the most necessarily sensitive areas of pastoral care is dealing with perinatal death. This case study grows from a need for care providers to understand better the feelings of a mother in the loss of her baby. This particular exploration evolved from a taped interview with the writer's aunt (now in her seventies) and her dealings with the multiple losses she experienced over fifty years ago. Her conversation in the interview gives credibility to many coping skills that we endeavor to teach today and that she developed for herself out of a need to survive.